2023
DOI: 10.1111/jocn.16866
|View full text |Cite
|
Sign up to set email alerts
|

Promoting activity and mobility in long‐term care environments: A photo‐elicitation study with older adults and nurses

Noora Narsakka,
Riitta Suhonen,
Barbara Groot
et al.

Abstract: Aim(s)The aim of this research study is to collaboratively generate insights in the current institutional long‐term care environment for activity and mobility of older adults, and of solutions that could be used to increase the activity and improve the mobility of the older adults.DesignThis research constitutes a qualitative study with a critical approach.MethodsData were collected using photo‐elicitation in four long‐term care units in Finland during the spring of 2022. Older adults participated in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It has been shown that when successful, exercise to improve muscle strength increases confidence to negotiate steps and other barriers. Older adults who exercise report increased freedom [79] for instance, they can leave the house and travel independently on public transport [80].…”
Section: Meanings Articulated Regarding Physical Exercise Post-covid-19mentioning
confidence: 99%
“…It has been shown that when successful, exercise to improve muscle strength increases confidence to negotiate steps and other barriers. Older adults who exercise report increased freedom [79] for instance, they can leave the house and travel independently on public transport [80].…”
Section: Meanings Articulated Regarding Physical Exercise Post-covid-19mentioning
confidence: 99%